Storytelling and Professional Learning - Brenton Doecke (International Conference on Languages and Arts, 2012)
This paper begins by reflecting on the role that story-telling plays in our lives, drawing on a range of theoretical resources to affirm the value of storytelling as ‘the central function or instance of the human mind’ (to borrow the words of Fredric Jameson, 1981, p.13). The paper then moves on to ask why story-telling is not given the prominence it deserves in school education, and then considers ways in which classrooms might be reconceptualized as storytelling sites, in which teachers and their pupils come together to share their experiences by exchanging stories. The main focus of the paper, however, is on the heuristic value of storytelling as a form of professional learning and practitioner inquiry. This will include reflecting on the importance of autobiographical writing as a vehicle through which educators can develop a reflexive practice that is sensitive to the values and beliefs of the young people they teach. I will also be looking at how teachers can learn by writing stories about their  day-to-day professional practice, drawing on my long-time collaboration with Douglas McClenaghan, an English teacher who works in a state school in Melbourne (Doecke and McClenaghan, 2011). To conclude the paper I will also consider the role that storytelling has played in a major project in which I have been engaged, namely the development of the Standards for Teachers of English Language and Literacy in Australia (STELLA), focusing on the teacher narratives published on the STELLA website (stella.org.au).A key aim of the paper is to show how teacher educators working in tertiary institutions and school teachers can develop collaborative research partnerships by focusing on the stories that teachers tell about their work.